The Linguostylistic and the Linguopoetic Study of Metaphor in D. H. Lawrence’s “Sons and Lovers” - Mkhitaryan, Irina (Armenian Folia Anglistika, 2008)
The article highlights the unique nature of the metaphors in D. H. Lawrence’s works from linguostylistic and linguopoetic perspectives. The detailed analysis reveals the crucial role metaphors play in the portrayal of characters created by the writer.